Photoconverting nets affect plant growth and levels of antiviral glucoevatromonoside and total cardenolides in Digitalis mariana ssp. heywoodii (P. Silva and M. Silva) Hinz - Marafeli, Érica Alves Marques; Chibli, Lucas Apolinário [UNESP]; Rocha, João Pedro Miranda; Assis, Rafael Marlon Alves de; Pinto, José Eduardo Brasil Pereira; Pádua, Rodrigo Maia de; Kreis, Wolfgang; Munkert, Jennifer; Braga, Fernão Castro; Bertolucci, Suzan Kelly Vilela (Elsevier, 2023)
Digitalis mariana ssp. heywoodii (P. Silva & M. Silva) Hinz is an important source of bioactive cardenolides, including the promising antiviral agent glucoevatromonoside (GEV). The influence of light on the contents of total cardenolides has been demonstrated for different species of Digitalis. This study evaluated the influence of light spectral quality on the vegetative growth and levels of photosynthetic pigments, total proteins, total cardenolides, and GEV in D. mariana ssp. heywoodii. The process of extraction and quantification of GEV was established using an analytical quality by design (AQbD) approach, applying experimental design and analytical validation. Seedlings were grown for 120 days under photoconverting nets with 50% shading in blue, red, and black colours and under full sun. The use of blue net, followed by red net, resulted in the highest contents of GEV, total cardenolides, proteins, photosynthetic pigments and dry matter in the plants, along with highest root length and leaf area. The advantage of using blue nets over full sun for cultivating D. mariana ssp. heywoodii, herein demonstrated, aggregates new information on the management of this subspecies and corroborates previous data reported for other Digitalis species.
Keywords: Antiviral cardenolide; Digitalis; Farming systems; Photosynthetic pigments; Spectral quality of light